2006
DOI: 10.1167/iovs.05-1427
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages Are Vital in Spontaneous Intraocular Tumor Eradication

Abstract: Local macrophages in the eye are involved in the process of spontaneous AC tumor eradication in mice. However, it is not conclusive from these data exactly how tumor-specific CD4+ T cells and macrophages interact with each other to eliminate the Ad5E1-AC tumor without any collateral eye damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
30
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 27 publications
4
30
0
Order By: Relevance
“…29 However, not all TAMs support the growth of tumors, as there are multiple accounts of macrophages being tumoricidal and necessary for tumor rejection. [30][31][32] This again underscores the heterogeneity of macrophage populations and their influence on tumor growth or progression.…”
Section: Macrophages and Angiogenesismentioning
confidence: 80%
“…29 However, not all TAMs support the growth of tumors, as there are multiple accounts of macrophages being tumoricidal and necessary for tumor rejection. [30][31][32] This again underscores the heterogeneity of macrophage populations and their influence on tumor growth or progression.…”
Section: Macrophages and Angiogenesismentioning
confidence: 80%
“…A previously described technique for deposition of tumor cells into the anterior chamber (AC) of the mouse was applied with slight modifications (15,17). Mice were anesthetized with a mixture (ratio 1:1) of xylazine (Rompun 2%, Bayer, Leverkussen, Germany) and ketamine hydrochloride (Aescoket, Aesculaap, Boxtel, The Netherlands), given i.p.…”
Section: Intracameral Inoculation and Clinical Evaluationmentioning
confidence: 99%
“…We studied tumor growth postremoval of macrophages in an ocular tumor model (15)(16)(17). Because EspinosaHeidmann and Apte (7,8) showed that age influences macrophage polarization, we also determined whether tumor growth was different in young versus old mice and what the effect of macrophage depletion would be on tumor progression at different ages.…”
mentioning
confidence: 99%
“…CTL activity in both studies was not detected toward the respective target cells even though a mononuclear cell infiltrate was observed in rejecting tissue, and the processing and presentation of relevant peptides by host APCs were necessary to generate CD8 ϩ T effector cells (45). It bears noting that F4/80 ϩ macrophages are involved in rejecting Ad5E1 intraocular tumors (data not shown) and that the depletion of ocular macrophages with clodronate liposome injection results in progressive Ad5E1 tumor growth (11). This suggests that ocular APC function may be necessary for tumor Ag presentation to CD8 ϩ T cells and eventual tumor rejection in the eye.…”
Section: Discussionmentioning
confidence: 86%
“…However, ocular immune privilege can be circumvented. Ocular tumors can induce a robust systemic immune response that culminates in tumor rejection (7)(8)(9)(10)(11). Immune rejection of intraocular tumors follows two mutually divergent patterns.…”
mentioning
confidence: 99%